Pengaruh Literasi Keuangan Dan Layanan Keuangan Berbasis Teknologi Terhadap Inklusi Keuangan (Studi Kasus pada UMKM di Kabupaten Demak) - Astohar Astohar; Mirna Dyah Praptitorini; Siti Shobandiyah (Edumedia Solution, 2022)
The development of fintech has led to several application innovations in financial services such as payment instruments, loan tools and others that are becoming known in this digital era. Some business actors such as MSMEs in Demak Regency have also used this financial technology (fintech) for the convenience of running a business. The survey results show that MSMEs are still not optimal in the use of fintech as well as the level of inclusion is still relatively low. The problem in this study is that there is a gap regarding the effect of financial literacy and technology-based fintech services on financial inclusion. The population in this study were all MSMEs in Demak Regency. Collecting data using cross section data with sampling method using accidental sampling. The analysis tool uses double step multiple regression by performing other tests such as normality test, classical assumption deviation test, goodness of fit test and coefficient of determination test. The results show that financial literacy has a significant positive effect on financial inclusion (H1 is proven) fintech-based financial services have a significant positive effect on financial inclusion (H2 is proven). This increasingly complex business world has an impact on the demands or desires of business people for speed in transactions which are constrained by distance and time. Increased knowledge and behavior as well as attitudes in the financial sector have an impact on the fulfillment of technology-based financial services as well as on increasing the use of financial applications